2011
DOI: 10.1016/j.devcel.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

LC3 and GATE-16 N Termini Mediate Membrane Fusion Processes Required for Autophagosome Biogenesis

Abstract: Autophagy is a unique membrane trafficking pathway describing the formation and targeting of double membrane autophagosomes to the vacuole/lysosome. The biogenesis of autophagosomes and their delivery to the vacuole/lysosome depend on multiple membrane fusion events. Using a cell-free system, we have investigated the ability of LC3 and GATE-16, two mammalian Atg8 orthologs, to mediate membrane fusion. We found that both proteins promote tethering and membrane fusion, mediated by the proteins' N-terminal α heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
244
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(255 citation statements)
references
References 39 publications
8
244
1
2
Order By: Relevance
“…To investigate the functional significance of the GTP-dependent structural transitions, we monitored potential s-Mgm1 membrane fusion activity using a well characterized NBD-rhodamine lipid mixing assay (24,29). We showed that s-Mgm1 promoted IM lipid mixing in a dose-dependent manner independently of nucleotide (Fig.…”
Section: S-mgm1 Lipid-bound Oligomers Undergo a Nucleotide-dependent mentioning
confidence: 99%
“…To investigate the functional significance of the GTP-dependent structural transitions, we monitored potential s-Mgm1 membrane fusion activity using a well characterized NBD-rhodamine lipid mixing assay (24,29). We showed that s-Mgm1 promoted IM lipid mixing in a dose-dependent manner independently of nucleotide (Fig.…”
Section: S-mgm1 Lipid-bound Oligomers Undergo a Nucleotide-dependent mentioning
confidence: 99%
“…43 Upon autophagosome closure, the LC3-II on the outer surface of the autophagosome is cleaved from PE and released back into the cytosol, along with the other ATG proteins; the LC3-II that is present on the concave surface remains associated with the completed autophagosome. [44][45][46] As a consequence, LC3-II has widely been used as an autophagic marker. 47,48 The final stage of autophagy is initiated by autophagosome-lysosome fusion, a process recently shown to involve interaction between STX17 (syntaxin 17) as an autophagosomal soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) with its targets SNAP29 and VAMP8, which drives the fusion between the outer autophagosomal membrane and the lysosomal membrane.…”
Section: The Process and Regulation Of Autophagymentioning
confidence: 99%
“…In addition to its interaction with polyUb chains, p62/SQSTM1 interacts directly with the UBL proteins LC3/GABARAPs, which are conjugated to phosphatidylethanolamine enriched in autophagic membranes. Membrane-conjugated LC3/GABARAPs mediate lipid bilayer tethering and hemifusion (15,16), drive expansion of autophagosomes, and via autophagic receptors, target autophagy cargo to the endolysosomal compartment (17). p62/SQSTM1 binds LC3/GABARAPs via a short linear sequence, designated the LC3-interacting region (LIR) and broadly defined by the core sequence (W/F/Y)XX(L/I/V), where X is any amino acid (aa) (13,18).…”
Section: Ufm1mentioning
confidence: 99%